Determination of the average lifetime of b-baryons - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; et al. (2011)
The average lifetime of b-baryons has been studied using 3 × 106 hadronic Z0 decays collected by the DEL-PHI detector at LEP. Three methods have been used, based on the measurement of different observables: the proper decay time distribution of 206 vertices reconstructed with a A, a lepton and an oppositely charged pion; the impact parameter distribution of 441 muons with high transverse momentum accompanied by a A in the same jet; and the proper decay time distribution of 125 A0-lepton decay vertices with the A, exclusively reconstructed through its pKπ, pK0 and A3π decay modes. The combined result is:, where the first systematic error is due to experimental uncertainties and the second to the uncertainties in the modelling of the b-baryon production and semi-leptonic decay. Including the measurement recently published by DELPHI based on a sample of proton-muon vertices, the average b-baryon lifetime is T (b-baryon) = (1.255+0.115-0.102(stat)0102 ± 0.05) ps. © Springer-Verlag 1996.